Sarcoidal granuloma presenting on tattoo: a report of a Japanese female patient and a review of Japanese published work - Ohtsuka, Mikio; Natsuko, Matsumura; Toshiyuki, Yamamoto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Cases of tattoo sarcoidosis reported in English and French literature have recently been reviewed; however, only two Japanese patients were included in the review because most Japanese patients were reported in Japanese journals. Objectives: To determine the clinical characteristics of Japanese tattoo sarcoidosis. Methods: We reported a Japanese female with tattoo sarcoidosis, and reviewed the cases of tattoo sarcoidosis reported in Japanese literature. Results: A 27-year-old Japanese female presented with skin nodules on a tattoo. She was diagnosed as having systemic sarcoidosis by skin biopsies and systemic work-up. We identified twelve cases, including ours, with tattoo sarcoidosis reported in Japanese journals, and revealed that these cases showed clinical features closely similar to those of Japanese sarcoidosis without tattoo in terms of the onset age distributions, incidence of extracutaneous organ involvement, and laboratory abnormalities. In comparison with cases of other races, Japanese tattoo sarcoidosis was revealed to have a higher prevalence of uveitis, which might be attributable to genetic background, as incidence and organ involvement may vary from race to race. Conclusions: Our results suggest that a tattoo does not have significant impact on the clinical features of sarcoidosis. However, skin lesions on a tattoo can be the first sign of systemic sarcoidosis in any race; therefore, much attention should be paid to skin eruptions on a tattoo for earlier identification of patients who need work-up for systemic illness.